Analisis Pengelolaan Pengaduan Masyarakat melalui Aplikasi JAKI dalam Rangka Pelayanan Publik di DKI Jakarta - Haekal, Muhammad; Tjenreng, Muhammad Baharuddin Zubakhrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research discusses the functions of government in public service delivery and community empowerment based on Ndraha's theory (2003). The primary functions of government include high-quality public services, while secondary functions focus on community empowerment. Law No. 25 of 2009 regulates public complaint mechanisms as a form of public participation to improve service quality. The Jakarta Kini (JAKI) application, developed by the DKI Jakarta Provincial Government, serves as a smart governance-based platform for managing public complaints. JAKI's results indicate a 97.9% resolution rate, with 89% of complaints submitted through the application. Challenges such as digital literacy and technical issues need to be addressed to ensure JAKI remains effective in achieving transparent, responsive public services based on good governance principles.